Safety Improvements through Lessons Learned from Operational Experience in Nuclear Research Facilities - Lambert, Francis; Volkov, Yuri (Nato Security through Science Series B, Physics and Biophysics, 2006)
For operators of nuclear research facilities, it is of particular importance to investigate minor incidents: indeed, as safety demonstrations are generally based on the presence of several independent "lines of defence", only through attentive investigation of every occurrence, usually minor and of no consequence, can the level of trust placed in each of these defensive lines be confirmed, or the potential risks arising out of a possible weakness in the system be anticipated. The efficiency of the system is based on a rigorous procedure: stringent attention to all incidents, consideration of the potential consequences of the incidents in their most pessimistic scenarios, and promotion of a broad conception of transpositions of the events, in time and space, for experience feedback. This efficiency presumes motivation on the part of all those involved, hence the importance of dissociating from the concept of an "incident" any notion of "error" or "blame" both in internal analysis and in public communications. The nuclear industry has developed some very progressive tools for experience feedback, which could interest also management of other technological risks. This book presents the proceedings of a NATO Advanced Workshop dedicated to this important matter of concern.